2011
DOI: 10.1111/j.1365-2672.2011.05168.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and classification of toxigenic Staphylococcus aureus isolated from refrigerated ready-to-eat foods (sushi, kimbab and California rolls) in Korea

Abstract: Aims:  To investigate the presence of toxigenic Staphylococcus aureus in ready‐to‐eat (RTE) Korean foods and determine the distribution of genes related to various types of toxin production. Methods and Results:  A total of 3293 commercial RTE refrigerated foods (sushi, n = 1882; kimbab, n = 975; California rolls, n = 436) were collected from Korean grocery stores, department stores and convenience stores between January 2006 and June 2007. Of these, 197 (5·98%) RTE samples were contaminated with coagulase‐pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
0
18
1
2
Order By: Relevance
“…The enterotoxin genes in S. aureus have been reported by many studies (7,15,19), and the prevalence of strains bearing enterotoxin genes varied in these reports. We found that 55.5% of S. aureus isolates were positive for one or more SE genes, which was higher than the rate (49.8%) of the isolates with toxigenic properties in Korea but lower than the 85.0% rate reported in the United States (6,13). SEA, alone or together with other staphylococcal enterotoxins, is most frequently involved in food poisoning outbreaks worldwide, followed by SEB, SEC, or SED.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The enterotoxin genes in S. aureus have been reported by many studies (7,15,19), and the prevalence of strains bearing enterotoxin genes varied in these reports. We found that 55.5% of S. aureus isolates were positive for one or more SE genes, which was higher than the rate (49.8%) of the isolates with toxigenic properties in Korea but lower than the 85.0% rate reported in the United States (6,13). SEA, alone or together with other staphylococcal enterotoxins, is most frequently involved in food poisoning outbreaks worldwide, followed by SEB, SEC, or SED.…”
Section: Discussioncontrasting
confidence: 57%
“…However, without hygienic measures during prep aration, retailing, and consumption, RTE foods can be easily contaminated with microorganisms such as Escherichia coll, Salmonella, Listeria, and S. aureus (8). Moreover, the existence of S. aureus in RTE food has been reported by many countries, such as Korea, Brazil, and Vietnam (5,6,14). Few studies about the existence of S. aureus in RTE foods in the People's Republic of China have been reported.…”
mentioning
confidence: 95%
“…Food operation environments have major effects on the microbial contam ination of final food products (7,36), but most previous studies have been concerned with commercially manufac tured and prepacked products sold in retail markets or with RTE foods from street vendors (11,14,17,27,28,39). The present study was conducted to evaluate the microbiological quality of sandwiches prepared on site and served in bakeries, cafes, and sandwich bars.…”
Section: Discussionmentioning
confidence: 99%
“…One chicken-based sandwich had a very high level of contamination with both B. cereus (5.0 log CFU/g) and S. aureus (3.2 log CFU/g); however, these contaminations probably did not occur simultaneously because their sources are generally very different (B. cereus is associated with bread or raw materials from soils and sediments; S. aureus is associated with unsanitary food handlers) (25,26,28,42). Two samples with Salmonella at > 4 log CFU/g also had a high potential for causing salmonellosis (infective dose is 5 to 10 log CFU/g) (32).…”
Section: Discussionmentioning
confidence: 99%
“…Laver has a high potential for contamination with microorganisms because of its cultivation environment (8,10). Some researchers have reported that dried laver is a major source of bacterial contamination in the well-known ready-to-eat food kimbab and in rolled sushi (1,11,12). However, to the best of our knowledge, there have been no previous investigations of the potential microbiological hazards present in processed laver products from real processing lines.…”
mentioning
confidence: 99%